Ubiquitin and TFIIH-stimulated DDB2 dissociation drives DNA damage handover in nucleotide excision repair - Cristina Ribeiro-Silva (Nature Portfolio, 2020)
DNA damage sensors DDB2 and XPC are fundamental factors to initiate global genome nucleotide excision repair and protect DNA from mutagenesis. Here the authors reveal that ubiquitin and TFIIH-stimulated DDB2 dissociation promotes DNA damage handover to XPC in nucleotide excision repair.